A Review on Antioxidant Capacity of Malaysian Herbal Plants as Potential Wound Healing Therapy and Evaluation on Consumers Acceptance Towards Herbal Cream: English - Ezal Ain, Ezzah Norizni Ain; Mansur, Sity Aishah; A Razak, Aliff Hisyam (Progress in Engineering Application and Technology, 2021)
Wound healing is the result of a complex interaction of biological responses that repair damaged tissue. Emerging modern diseases have resulted in massive changes in medical treatment, with conventional treatment becoming less relevant and more expensive for modern infections. Thus, research on plant-derived compounds with therapeutic properties has been extensively studied to develop new drugs. Therefore, this study focuses on the identification of potential medicinal plants with wound healing abilities, including their antioxidant related substances and their mechanistic pathways. The Hedonic test was also used in this study to assess consumers' overall acceptability of herbal creams. For the identification of potential wound healing plants, several selected literatures were searched on electronic databases such as ResearchGate, ScienceDirect, Google Scholar, Scopus, Academic Journal Organization, PubMed, National Center for Biotechnology Information (NCBI) and Hindawi. The findings found that there are four antioxidant compounds that contribute to activation of Nrf2 signalling pathways and induce an antioxidant response element. These antioxidant compounds are curcumin, cinnamaldehyde, quercetin and kaempferol. All of these compounds may be present in Chromolaena odorata (pokok kapal terbang), Cinnamomum cassia (kulit kayu manis), Hibiscus rosa-sinensis (bunga Hibiscus), Curcuma longa (kunyit), Kaempferia galanga (cekur), and Hibiscus Sabdariffa (roselle). Finally, an assessment of consumers' overall acceptability of herbal creams reveals a significant trend of acceptance towards herbal cream application among consumers in 20’s The data analysis revealed that the age factor had an effect on overall acceptability. In conclusion, this research may provide insight and information regarding the effects of antioxidant properties and potential mechanistic pathways in incorporating plant-derived wound healing cream.